CT-guided biopsy of lung lesions: defining the best needle option for a specific diagnosis - Guimarães, Marcos Duarte (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2014)
OBJECTIVES: To evaluate the performance of fine and cutting needles in computed tomography guided-biopsy of lung lesions suspicious for malignancy and to determine which technique is the best option for a specific diagnosis. METHODS: This retrospective study reviewed the data from 362 (71.6%) patients who underwent fine-needle aspiration biopsy and from 97 (19.7%) patients who underwent cutting-needle biopsy between January 2006 and December 2011. The data concerning demographic and lesion characteristics, procedures, biopsy sample adequacy, specific diagnoses, and complications were collected. The success and complication rates of both biopsy techniques were calculated. RESULTS: Cutting-needle biopsy yielded significantly higher percentages of adequate biopsy samples and specific diagnoses than did fine-needle aspiration biopsy (p<0.05). The sensitivity, specificity, and accuracy of cutting-needle biopsy were 93.8%, 97.3%, and 95.2%, respectively; those of fine-needle aspiration biopsy were 82.6%, 81.3%, and 81.8%, respectively (all p<0.05). The incidence of pneumothorax was higher for fine-needle aspiration biopsy, and that of hematoma was higher for cutting-needle biopsy (both p<0.05). CONCLUSIONS: Our experience using these two techniques for computed tomography-guided percutaneous biopsy showed that cutting-needle biopsy yielded better results than did fine-needle aspiration biopsy and that there was no significant increase in complication rates to indicate the best option for specific diagnoses.